(3GdOhGFQ hTQMgGs - (3eMeO Hf WdMIs
(3ChdgG (B:s
(3GYde Cf gPg GdOGFQI bLO GMJhJ Ydi eG jXgQ aj Gdchf ef Gdedhc hGdMcGe s
(3BNQgG (B:s
(3hMQha GdBjJjf GdoeJbGHdJjf NGQL GdOFQI hVQH GdeLehY aj MQha GdQehR jchf GdeWdhH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQcRjI GdYGeI (B- (3GdehUd (B(302 (3L(B) s
Keywords: (3GdMQha h GdChaGbs